Environmental, social and governance (ESG) disclosure and cost of equity: the moderating effects of board structures - Rosmiati Jafar; Basuki Basuki; Windijarto Windijarto; Rahmat Setiawan; Zulnaidi Yaacob (Cogent Business & Management, 2024)
One of the main issues in the field of sustainable finance is environmental, social, and governance (ESG). This study examines how ESG disclosure impacts the cost of equity. Additionally, it explores how the structure of the board of commissioners moderates this relationship. The structure of the board of commissioners is represented by three key factors: the proportion of independent commissioners, the board of commissioners's size, and the proportion of female commissioners. The sample used in this research was 215 non-financial companies that published sustainability reports (SR) and were listed on the Indonesia Stock Exchange (BEI) with research years 2017, 2021, and 2022 with a total of 309 observations. The research employed Ordinary Least Square (OLS) and Moderated Regression Analysis (MRA) to test the hypotheses. The findings indicate that ESG disclosure negatively impacts the cost of equity. Additionally, the study reveals that a higher proportion of independent commissioners, a larger board of commissioners's size, and a greater proportion of female commissioners mitigate company risk. These factors weaken the negative effect of ESG disclosure on the cost of equity by substituting its risk-reducing benefits. The results of these findings were further validated through additional moderating variable analysis techniques. Specifically, subgroup analysis and regression models incorporating a one-year lag for the ESG variables were employed, yielding consistent results.
Keywords: 650; ESG disclosure; cost of equity; board of commissioners; board structures; independent commissioners; board of commissioners' size; female commissioners; sustainable finance